Adenosine A(1), A(2a), A(2b), and A(3) receptors in hematopoiesis. 2. Expression of receptor mRNA in resting and lipopolysaccharide-activated mouse RAW 264.7 macrophages - Štreitová, D; Hofer, M; Holá, J; Vacek, A; Pospíšil, M (Physiological research, 2010)
Expression of mRNA for adenosine receptor subtypes A(1), A(2a), A(2b), and A(3) in normal and lipopolysaccharide (LPS)-activated murine RAW 264.7 macrophages has been investigated using the method of quantitative real-time polymerase chain reaction. The results have shown a very low, unquantifiable expression of adenosine A(1) receptor mRNA in both normal and LPS-activated macrophages. The other three adenosine receptor mRNAs have been found to be expressed at various but always quantifiable levels. Activation of the macrophages by LPS induced upregulation of the expression of adenosine receptor A(2a) and A(2b) mRNA, whereas the expression of adenosine receptor A(3) mRNA was downregulated. Unstimulated macrophages exhibited a high expression of the A(2b) adenosine receptor mRNA. The findings are discussed from the point of view of the antiinflammatory and hematopoiesis-stimulating roles of the adenosine receptor signaling.
Keywords: messenger RNA; purinergní receptory P1; lipopolysacharidy; regulace genové exprese; Hematopoiesis; Lipopolysaccharides; Macrophage Activation; makrofágy; Receptor, Adenosine A2A; Receptor, Adenosine A2B; receptor adenosinový A2A; zvířata; myši; časové faktory; Mice; buněčné linie; hematopoéza; RNA, Messenger; Gene Expression Regulation; aktivace makrofágů; Cell Line; Receptors, Purinergic P1; polymerázová řetězová reakce; Polymerase Chain Reaction; receptor adenosinový A2B; Animals; receptor adenosinový A1; Macrophages; Time Factors; Receptor, Adenosine A3; Receptor, Adenosine A1; receptor adenosinový A3